PSYCHOLOGICAL INTOLERANCE TO IMPLANTABLE CARDIOVERTER DEFIBRILLATOR - Korpas, David (Biomedical papers, 2008)
Background: Implantable cardioverter defibrillators (ICD) are mobile implantable cardiac devices for immediate treatment of live threatening ventricular arrhythmias. However, these devices can affect patients, physiologically, psychologically and have effects on electrical devices.Case report: The case of a 61-year-old patient is reported. The patient came for regular 3-months visits with his ICD and complained about electromagnetic interference with all household electrical appliances, especially refrigerator and digital television set-top box. He described several phantom shocks when he came close to the electrical appliances. He noted the exact times and symptoms of the episodes but the device memory did not record anything.Conclusion: This case demonstrates the rare occurrence of psychological intolerance to implanted ICD shortly after implant. The device was programmed for higher sensitivity. The patient was calmed and reassured about the reprogramming.
Keywords: Implantable cardioverter defi brillator/Electrical interference/Psychological intolerance